PERBANDINGAN TEKNIK PEMAJANGAN SAYURAN DAUN UNTUK MEMPERTAHANKAN KESEGARAN SELAMA PENJUALAN - Sri Wahyuni; Sugeng Triyono; Ahmad Tusi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
This study aimedto observe the effect of soakingthe root of leafy vegetableson thefreshnessduringsale.  Vegetablesused werekangkungandgreen mustardfrom hydroponicsandconventionalcultivations.  Treatments wereconsistedofsoakingwithaeratedwater, soakingwithunaeratedwater, soaking withaerated nutrient solution(EC 0.4mS/cm), displaying in mist sprayed (humidified) cabinet without soaking,andcontrol(neither soaking nor spraying).  Soakingwas donein aglasscontainer(50cm length, 40cm width, 20cm height)andfilledwithwater±20liters/5 cm height.  Parametersmeasured werewater content, leaf water potential,andleafdiscoloration.  The results showedthatthe average room temperature and RH were found about 29oC and 80%. Respectively temperature and RH in the humidified cabinet were not much different from the ambiance.  Soakingwithaeration was able to keep vegetables fresh without wilting process.  Percentage of yellowing reached 10% of the total number within 5days for hydroponics kangkung, 2 days for conventional kangkung, 4days for hydroponics green mustard, and 2 days for conventional green mustard during the display.  Vegetables displayed in the room with no treatment (control) were wilting consistently, their water content was decreasing, and their water potential tended to increase from the beginning.  Thus, discoloration was more proper parameter for the soaked vegetables, while change of water content and water potential were more proper for non soaked or spayed vegetables. Keywords: Aerated, display, leafy vegetables, soaking